The Relationship Between Family Function and Aggressive Behavior Among Adolescents in Bandung City - Novya Ashlahatul Mar’ah; Tira Arrahman; Wini Hadiyani (LPPM UNIKAL, 2025)
Introduction: Aggressive behaviour in adolescents is an increasing problem, with negative impacts on both individuals and society. Optimal family functioning can help adolescents manage emotions and reduce aggressive behaviour. Objectives: This study aims to determine the relationship between family function and aggressive behaviour among adolescents in Bandung City. Methods: This research was descriptive correlation with a cross-sectional study design. The total samples were 140 respondents selected by using convenience technique sampling. Data were collected using the Buss-Perry Aggressive Behaviour Questionnaire (BPAQ) and the Family Assessment Device (FAD) to measure family functioning. Data were analysed using the Pearson correlation test. Results: The analysis showed a negative relationship between family function and aggressive behaviour, with a correlation value of R = -0.287 and a significance level of p < 0.001, which indicated that the more optimal the family function, the lower the aggressive behaviour in adolescents. Conclusion: These findings confirm the important role of family in shaping adolescent behaviour and reducing aggressive behaviour. Optimizing increased family functioning, which includes more effective communication, emotional support, and better conflict management, can contribute to a decrease in aggressive behaviour in adolescents.